Acute toxicity of chemically enhanced water accomodated fraction (CEWAF) of Petron Bunker Oil on Nile Tilapia, Oreochromis niloticus (L.) fry. - Ledesma, Kristine Claire P.
Acute toxicity of Petron Bunker C oil chemically enhanced water-accomodated fraction (CEWAF) on fry of Nile Tilapia, Oreochromis niloticus (mean length 1 cm), was tested through static 48-hour bioassay. Median lethal concentration (LC50) was computed and the sublethal responses were noted. Results showed that increasing concentrations of Petron Bunker C Oil CEWAF caused increasing mortality. 48-hour LC50 value was 0.26 percent v/v. sublethal effects of CEWAF on O. niloticus included lethargy, impaired swimming, curved backbone, and loss of buoyancy.